INCREASING THE ECONOMIC VALUE OF TEMPE BUNGKIL INNOVATION PRODUCTS THROUGH DIVERSIFICATION AND DIGITAL MARKETING TRAINING IN PAKISAJI MALANG - Agustina, Rini; Meviana, Ika; Rusno, Rusno; Alim Ba'diya Kusufa, Roni; Trio Agus Muslim, Lanyala; Hanella Putri, Evina (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Background: Tempe bungkil is a processed by-product of soybean oil production that has high nutritional and economic potential, but has not been optimally utilized by MSMEs in Legok Sukoraharjo Village, Pakisaji District, Malang Regency. Problems faced by partners include: (1) production that is still traditional and highly dependent on weather conditions, (2) lack of product diversification, (3) simple packaging, and (4) marketing that is still limited to conventional methods. Method: The community service method used is participatory training involving MSMEs and the community. The activity stages include: (1) socialisation of the potential and benefits of tempe bungkil, (2) product innovation training (nuggets, crackers, frozen food), (3) modern packaging training with standing pouches, (4) digital marketing training, and (5) evaluation. Results: The results of the activity show a significant increase in partner capacity. Analysis of sales data 2 months post-training shows an increase in income of 45.8% from an average of IDR 1,200,000/week to IDR 1,750,000/week. The impacts felt are increased income, expanded market reach through online sales (15% of total sales), and the creation of new, more sustainable business opportunities and reduced dependence on the weather.